Algorithmic Culture and E-Literary Text Semiotics. - Strehovec, Janez (Cultura: International Journal of Philosophy of Culture & Axiology (15841057), 2013)
This paper aims to explore the notion of algorithmic culture in relation to new media and electronic literature. Such a culture considers human as being immersed in smart technology, which with its code and algorithms defines individual's behaviour and decision-making, modes of socializing and participation, experiencing and perception. The following lines unveil the paradigm shift that involves semiotic crossings between human and machine languages. In order to do so, it addresses some crucial particularities of the emerging field of electronic literature.